Gibberellins negatively regulate the development of Medicago truncatula root system. - Fonouni-farde, Camille Audrey (2019)
The root system displays a remarkable plasticity that enables plants to adapt to changing environmental conditions. This plasticity is tightly linked to the activity of root apical meristems (RAMs) and to the formation of lateral roots, both controlled by related hormonal crosstalks. In Arabidopsis thaliana, gibberellins (GAs) were shown to positively control RAM growth and the formation of lateral roots. However, we showed in Medicago truncatula that GAs negatively regulate root growth and RAM size as well as the number of lateral roots depending at least on the MtDELLA1 protein. By using confocal microscopy and molecular analyses, we showed that GAs primarily regulate RAM size by affecting cortical cell expansion and additionally negatively regulate a subset of cytokinin-induced root expansin encoding genes. Moreover, GAs reduce the number of cortical cell layers, resulting in the formation of both shorter and thinner roots. These results suggest contrasting effects of GA regulations on the root system architecture depending on plant species.